Efektivitas Edukasi Cuci Tangan Pakai Sabun (CTPS) terhadap Upaya Pencegahan Diare di Kota Mataram - Kumarayanti, Ni Komang Dessy; Asmara, I Gede Yasa; Artastra, I Ketut (Faculty of Medicine Universitas Mataram, 2020)
Research Background: Diarrhea is an abnormal bowel movement with a liquid consistency and more frequent passage than normal. Diarrhea in Indonesia is still an endemic disease and potential to be an outbreak events which causing death. Diarrhea can be prevented by community-led total sanitation (CLTS) that consist of 5 programs, one of them is hand washing with soap. The purpose of this study was to determine the effectiveness of hand washing with soap education on the changes in knowledge and attitude of respondents to prevent diarrhea. Method:The design of the study was One Group Pre test – Post test with purposive sampling.The subject of this study were 114 mothers who have children under five year of age at posyandu around Cakranegara Primary Health Care. Result:The result of the study found increasing in percentage of respondent who had high knowledge about 47,37% from 59 respondents (51,75%) before intervention to 113 respondents (99,12%). It was also found an increase in percentage of respondent who have good attitude about 7,9% from 102 respondents (89,47%) before intervention to 111 respondents (97,37%). Conclusion:Hand washing with soap education was effective to improve knowledge and attitude of respondent in order to prevent diarrhea with p < 0,001.